The dead phosphatases society: a review of the emerging roles of pseudophosphatases. (16th June 2020) - Reiterer, Veronika; Pawłowski, Krzysztof; Desrochers, Guillaume; Pause, Arnim; Sharpe, Hayley J.; Farhan, Hesso
Abstract : Phosphatases are a diverse family of enzymes, comprising at least 10 distinct protein folds. Like most other enzyme families, many have sequence variations that predict an impairment or loss of catalytic activity classifying them as pseudophosphatases. Research on pseudoenzymes is an emerging area of interest, with new biological functions repurposed from catalytically active relatives. Here, we provide an overview of the pseudophosphatases identified to date in all major phosphatase families. We will highlight the degeneration of the various catalytic sequence motifs and discuss the challenges associated with the experimental determination of catalytic inactivity. We will also summarize the role of pseudophosphatases in various diseases and discuss the major challenges and future directions in this field. Abstract : Phosphatases are signaling enzymes that remove phosphate from proteins, lipids and other cellular components. A significant fraction of the human phosphatases bear mutations in one or several catalytic motifs. These members are referred to as pseudophosphatases and are present in most subfamilies of the phosphatome. In this review, we systematically catalogue the pseudophosphatases, illustrate the degeneration of their catalytic motifs and discuss their roles in health and disease.